2021
DOI: 10.1186/s13046-021-01843-8
|View full text |Cite
|
Sign up to set email alerts
|

USP16 regulates castration-resistant prostate cancer cell proliferation by deubiquitinating and stablizing c-Myc

Abstract: Background c-Myc, a well-established oncogene, plays an important role in the initiation and progression of various cancers, including prostate cancer. However, its mechanism in cancer cell remains largely unknown and whether there exist a deubiquitinase targeting c-Myc also remains elusive. Methods Bioinformatic analysis and shRNA screening methods were used to identify potential deubiquitinases that correlate with c-Myc gene signature. Cell proli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…There are other DUBs excluded from this paper for the same reason as described. DUBs which affect c-Myc are CYLD [136], USP2a [137][138][139], USP7 [140,141], USP13 [142], USP16 [143], USP18 [144], USP22 [145,146], USP28 [147], USP36 [148,149], and OTUD6B isoform 2 [150]. DUBs that regulate FBP1 include USP22 [151] and USP44 [114].…”
Section: Other Dubsmentioning
confidence: 99%
“…There are other DUBs excluded from this paper for the same reason as described. DUBs which affect c-Myc are CYLD [136], USP2a [137][138][139], USP7 [140,141], USP13 [142], USP16 [143], USP18 [144], USP22 [145,146], USP28 [147], USP36 [148,149], and OTUD6B isoform 2 [150]. DUBs that regulate FBP1 include USP22 [151] and USP44 [114].…”
Section: Other Dubsmentioning
confidence: 99%
“…The MYC gene was a proto-oncogene, which has been studied for many decades ( Cole and McMahon, 1999 ). A recent study showed that MYC could be regulated by USP16, which further inhibited prostate cancer progression ( Ge et al, 2021 ). MYC was also found to participate in angiogenesis ( MeĆĄkytė et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining was performed with EIF4A1 antibody (ab31217, Abcam) following the previous protocol ( 23 ). The IHC scores were calculated by staining intensity and the percentage of stained cells as reported ( 24 ).…”
Section: Methodsmentioning
confidence: 99%